Citation Analysis Shows Promise as an Effective Tool for Monograph Collection Development - Marsalis, Scott (Evidence Based Library and Information Practice, 2010)
A Review of: Enger, K. B. (2009). Using citation analysis to develop core book collections in academic libraries. Library & Information Science Research, 31(2), 107-112. Objective – To test whether acquiring books written by authors of highly cited journal articles is an effective method for building a collection in the social sciences. Design – Comparison Study. Setting – Academic library at a public university in the US. Subjects – A total of 1,359 book titles, selected by traditional means (n=1,267) or based on citation analysis (n=92). Methods – The researchers identified highly-ranked authors, defined as the most frequently cited authors publishing in journals with an impact factor greater than one, with no more than six journals in any category, using 1999 ISI data. They included authors in the categories Business, Anthropology, Criminology & Penology, Education & Education Research, Political Science, Psychology, Sociology/Anthropology, and General Social Sciences. The Books in Print bibliographic tool was searched to identify monographs published by these authors, and any titles not already owned were purchased. All books in the study were available to patrons by Fall 2005. The researchers collected circulation data in Spring 2007, and used it to compare titles acquired by this method with titles selected by traditional means. Main Results – Overall, books selected by traditional methods circulated more than those selected by citation analysis, with differences significant at the .001 level. However, at the subject category level, there was no significant difference at the .05 level. Most books selected by the test method circulated one to two times. Conclusion – Citation analysis can be an effective method for building a relevant book collection, and may be especially effective for identifying works relevant to a discipline beyond local context.